2015
DOI: 10.1097/fpc.0000000000000116
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood IRF1 expression as a marker for glucocorticoid sensitivity

Abstract: Despite of the common usage of glucocorticoids (GCs), a significant portion of asthma patients exhibit GC insensitivity. This could be mediated by diverse mechanisms, including genomics. Recent work has suggested that measuring changes in gene expression may provide more predictive information about GC insensitivity than baseline gene expression alone, and that expression changes in peripheral blood may be reflective of that in the airway. Through gene expression omnibus (GEO) analysis, we identified IRF1 whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In this respect, roles for IRF1 and CXCL10 in innate immunity, anti-viral defenses, and in the development of Th1 immunity are suggested and may be promoted by DUSP1 (16,26,60). Conversely, enhanced IRF1 expression is linked and/or associated with reduced glucocorticoid sensitivity (18,19). This may reflect that IRF1-dependent responses are maintained in the presence of glucocorticoids and, therefore, appear resistant.…”
Section: Negative Regulation Of Irf1 By Mapksmentioning
confidence: 95%
See 1 more Smart Citation
“…In this respect, roles for IRF1 and CXCL10 in innate immunity, anti-viral defenses, and in the development of Th1 immunity are suggested and may be promoted by DUSP1 (16,26,60). Conversely, enhanced IRF1 expression is linked and/or associated with reduced glucocorticoid sensitivity (18,19). This may reflect that IRF1-dependent responses are maintained in the presence of glucocorticoids and, therefore, appear resistant.…”
Section: Negative Regulation Of Irf1 By Mapksmentioning
confidence: 95%
“…Thus, a loss of MAPK activity could contribute to the maintenance of IRF1 expression in the presence of glucocorticoids. This may play a role in glucocorticoid insensitivity, and indeed enhanced expression of IRF1 is implicated in reduced responsiveness to glucocorticoids (18,19).…”
mentioning
confidence: 99%
“…Recently, Chapin et al [41] indicated that the expression level of IRF1 was changed in the peripheral blood, which can be used as a marker to reflect the glucocorticoid response. IRF1 plays a key role in response to pressure or volume overload, which is involved in the pathogenesis of ischemic heart diseases [42].…”
Section: Discussionmentioning
confidence: 99%
“…significantly elevated in the GR-C3 knockin spleens. Many of these genes and associated signaling pathways are known to be repressed by glucocorticoids (18)(19)(20)(21). Therefore, the inability of GR-C3 to fully counteract the LPSmediated rise in their expression suggests that additional GR translational isoforms are required for effective inhibition and resolution of inflammation.…”
Section: Rescued Female Gr-c3 Knockin Mice Have Altered Circadian Rhythmmentioning
confidence: 99%